2021
DOI: 10.3390/cancers13030471
|View full text |Cite
|
Sign up to set email alerts
|

Lymphopenia as a Biological Predictor of Outcomes in COVID-19 Patients: A Nationwide Cohort Study

Abstract: We aimed to identify whether lymphopenia is a reliable prognostic marker for COVID-19. Using data derived from a Korean nationwide longitudinal cohort of 5628 COVID-19 patients, we identified propensity-matched cohorts (n = 770) with group I of severe lymphopenia (absolute lymphocyte counts [ALC]: <500/mm3, n = 110), group II of mild-to-moderate lymphopenia (ALC: ≥500–<1000/mm3, n = 330), and group III, no lymphopenia (ALC: ≥1000/mm3, n = 330). A significantly higher mortality rate was associated with ly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
96
3
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(120 citation statements)
references
References 35 publications
16
96
3
5
Order By: Relevance
“…With 16% death rate at day 28, the death rate is significantly lower in this group than in patients with documented SARS-COV-2 RT-PCR+; however, this death rate at day 28 is higher than standard population of cancer patients. 28 , 29 The current results confirm observations reported in our previous single-centre study. 18 In this patient population, death is considered to be mostly (>50%) related to the underlying malignancy as per investigators' assessment.…”
Section: Discussionsupporting
confidence: 92%
“…With 16% death rate at day 28, the death rate is significantly lower in this group than in patients with documented SARS-COV-2 RT-PCR+; however, this death rate at day 28 is higher than standard population of cancer patients. 28 , 29 The current results confirm observations reported in our previous single-centre study. 18 In this patient population, death is considered to be mostly (>50%) related to the underlying malignancy as per investigators' assessment.…”
Section: Discussionsupporting
confidence: 92%
“…According to several studies, lymphopenia occurs in 80% of patients with mild and 96% severe COVID-19 and is a prognostic marker of poor disease outcome [ 5 , 6 , 7 , 35 ]. However, the pathogenesis of lymphopenia in COVID-19 could have complex etiology and may include more than 10 putative mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…However, the pathogenesis of lymphopenia in COVID-19 could have complex etiology and may include more than 10 putative mechanisms. In particular, the development of lymphopenia in patients with COVID-19 could result from extrapulmonary dissemination and the direct effect of SARS-CoV-2 particles on the tissues of the mediastinal lymph nodes, which filter lymph flowing from the lung primary inflammatory focus, and spleen, as a significant human lymphoid organ [ 9 , 10 , 11 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent retrospective study evaluated an antiviral administration in 21 subjects affected by COVID-19 for a week who reported persistent fever and worsening of CT tomography evidence and hypoxia; the study reported a potential therapeutic efficacy of tocilizumab for this class of subject. Indeed, after treatment, in addition to the improvement of body temperature, respiratory function, imaging, and lymphopenia improved in most of the patients, with a normalization of inflammatory markers without a significant adverse event [128]. Based on this observation, a multicenter, single-arm, open-label, phase 2 study is currently ongoing but, as with the other drugs discussed here, larger trials are required with appropriate controls before science-based recommendations on use can be made [140].…”
Section: Tocilizumabmentioning
confidence: 93%